PERCEPTION OF CONTROL, DISEASE, AND VACCINE FOR COVID-19: THE EXAMPLE OF HEALTHCARE PROFESSIONALS - Havva KAÇAN; Gülşen Ulaş KARAAHMETOĞLU; Vasfiye BAYRAM DEĞER (Rojan GÜMÜŞ, 2022)
The study was conducted to examine the relation between control perception, disease perception, and vaccine perception of healthcare employees regarding Covid-19. The median and minmax scores of the participants in the sub-dimension of the disease perception scale were found to be 4.00 (1.33 - 5.00) for dangerousness and 4.00 (1.00 - 5.00) for contagiousness. The control perception scale scores of healthcare professionals were 2.50 (1.00 - 5.00) for macro-control, 3.00 (1.00 - 4.75) for micro-control, and 3.25 (1.00 - 5.00) for controllability. The score of a positive attitude toward the COVID-19 vaccine of the health employees who accepted to participate in the study was found as 4.00 (1.00 - 5.00) and the negative attitude score towards the vaccine was 3.40 (1.00 - 5.00). In our study, a statistically significant difference was found between positive attitudes towards the vaccine and professional experience scores (p<0.05). A statistically significant difference was also detected between the positive attitude scores of the participants towards the vaccine and the variables of direct contact with a COVID-19 patient and chronic disease status (p<0.05). It was determined that healthcare professionals had high Covid-19 disease and control perceptions and negative attitudes towards the vaccine. When the roles and responsibilities of immunization and health workers in controlling pandemics are considered, it is recommended to organize training programs to eliminate the doubts of healthcare employees regarding the safety and efficacy of the Covid-19 vaccine and to maximize the acceptance of the vaccine.